2018
DOI: 10.3174/ajnr.a5603
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Biopsies of the Cervical Spine: Technique, Histopathologic and Microbiologic Yield, and Safety at a Single Academic Institution

Abstract: Percutaneous CT-guided biopsy of the cervical spine is an effective and safe procedure with high diagnostic yield and can obviate open procedures for histopathologic and microbiologic analyses of patients with clinical and imaging findings concerning for infection or primary and metastatic osseous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 8 publications
2
31
1
3
Order By: Relevance
“…[8][9][10] However, there is scarcity of data when it comes to assessing the comparative efficacy of these drill systems in lytic and suspected infectious lesions. In lytic lesions, prior studies have shown the diagnostic yield ranging from 70% to 96%; 3,11,12 however, these studies have predominantly assessed the manual drill systems. One prior study 13 reported the diagnostic yield and radiation dose for battery-powered drill systems, however, without comparison with manual systems.…”
mentioning
confidence: 99%
“…[8][9][10] However, there is scarcity of data when it comes to assessing the comparative efficacy of these drill systems in lytic and suspected infectious lesions. In lytic lesions, prior studies have shown the diagnostic yield ranging from 70% to 96%; 3,11,12 however, these studies have predominantly assessed the manual drill systems. One prior study 13 reported the diagnostic yield and radiation dose for battery-powered drill systems, however, without comparison with manual systems.…”
mentioning
confidence: 99%
“…Complication rates are based on retrospective studies of CT-guided spine biopsies for infectious and noninfectious processes. These report major complication rates of less than 2%, with the most common major complications being retroperitoneal or paraspinal hematomas that are usually (47,50,(52)(53)(54)(55)(56)(57). Cases of transient and permanent neurologic deficits have been reported (52,58).…”
Section: Biopsy Overviewmentioning
confidence: 99%
“…Cases of transient and permanent neurologic deficits have been reported (52,58). Although critical structures such as nerves, blood vessels, and the airway are in particularly close proximity to the needle path for cervical spine biopsies, case studies report that major and minor complications are rare and do not occur at a higher rate than in biopsies of the thoracic or lumbar spine (54,58,59). (Figure 2A) (54).…”
Section: Biopsy Overviewmentioning
confidence: 99%
See 2 more Smart Citations